2018
DOI: 10.3329/bjch.v42i2.37758
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-laboratory Profile of Enteric Fever and Antibiotic Sensitivity Pattern in Hospitalized Children

Abstract: Abstract:Background: Enteric fever is endemic in Bangladesh. This is an important cause of morbidity and mortality in developing countries. The aim of the study was to evaluate the clinical and laboratory profiles, culture positivity rate and sensitivity pattern of Salmonella enterica.Methodology: This was an observational study carried out in a tertiary care hospital in Dhaka, Bangladesh during the period from January to December, 2017. Total 120 children who had enteric fever diagnosed either by positive blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Out of 91 patients, 83 (91%) were culture positive for S. typhi and 8 (9%) were culture positive for S. paratyphi. These findings are consistent with some earlier studies by Saha et al and Rahat et al24,25 Only culture positive patients were evaluated. Out of 91 patients, 51 were receiving ceftriaxone and forty (40) were receiving azithromycin.…”
supporting
confidence: 92%
“…Out of 91 patients, 83 (91%) were culture positive for S. typhi and 8 (9%) were culture positive for S. paratyphi. These findings are consistent with some earlier studies by Saha et al and Rahat et al24,25 Only culture positive patients were evaluated. Out of 91 patients, 51 were receiving ceftriaxone and forty (40) were receiving azithromycin.…”
supporting
confidence: 92%
“…20,21,22 Comparatively, a 2018 study in Bangladesh found an isolation rate of 63.33 percent, which was significantly higher than the present study. 23 This high rate of isolation may be due to the prevalence of automated blood culture techniques. Blood culture positivity rates among febrile cases have been reported to be 8.5%, 5%, and 4.2% in Vietnam, 5%, and 4.2% in Delhi, and 4% in Egypt, respectively, despite diverse population-based experiences of the occurrence of typhoid fever in these countries.…”
Section: Figure-iii: Bacterial Identification By Automated Blood Cult...mentioning
confidence: 99%